Isolated Rhodium Atoms Activate Porous TiO2 for Enhanced Electrocatalytic Conversion of Nitrate to Ammonia - Zhi Liang Zhao; Shaoxuan Yang; Shensong Wang; Zhe Zhang; Liang Zhao; Qi Wang; Xinyi Zhang (Advanced Science)
Abstract The direct electrochemical reduction of nitrate to ammonia is an efficient and environmentally friendly technology, however, developing electrocatalysts with high activity and selectivity remains a great challenge. Single‐atom catalysts demonstrate unique properties and exceptional performance across a range of catalytic reactions, especially those that encompass multi‐step processes. Herein, a straightforward and cost‐effective approach is introduced for synthesizing single‐atom dispersed Rh on porous TiO2 spheres (Rh1‐TiO2), which functions as an efficient electrocatalyst for the electroreduction of NO3− to NH3. The synthesized Rh1‐TiO2 catalyst achieve a maximum NH3 Faradaic efficiency (FE) of 94.7% and an NH3 yield rate of 29.98 mg h−1 mgcat−1 at −0.5 V versus RHE in a 0.1 M KOH+0.1 M KNO3 electrolyte, significantly outperforming not only undoped TiO2 but also Ru, Pd, and Ir single‐atom doped titania catalysts. Density functional theory calculations reveal that the incorporation of Rh single atom significantly enhances charge transfer between adsorbed NO3− and the active site. The Rh atoms not only serve as the highly active site for electrochemical nitrate reduction reaction (NO3RR), but also activates the adjacent Ti sites through optimizating the electronic structure, thereby reducing the energy barrier of the rate‐limiting step. Consequently, this results in a substantial enhancement in electrochemical NO3RR performance. Furthermore, this synthetic method has the potential to be extended to other single‐atom catalysts and scaled up for commercial applications.